VD_FINDINFO Jug / 2017 / 349 vom 5. November 2015 - VD Tribunal cantonal (2015)
ARRESTATION, RISQUE DE FUITE, RISQUE DE RÉCIDIVE, DÉTENTION POUR DES MOTIFS DE SÛRETÉ | 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 232 CPP (CH), 237 CPP (CH)